Pro Entity Framework Core 2 for ASP.NET Core MVC - Freeman, Adam (Apress, 2018)
Model, map, and access data effectively with Entity Framework Core 2, the latest evolution of Microsoft's object-relational mapping framework that allows developers to access data using .NET objects, and the most common data access layer used in ASP.NET Core MVC 2 projects. Best-selling author Adam Freeman explains how to get the most from Entity Framework Core 2 in MVC projects. He begins by describing the different ways that Entity Framework Core 2 can model data and the different types of databases that can be used. He then shows you how to use Entity Framework Core 2 in your own MVC projects, starting from the nuts-and-bolts and building up to the most advanced and sophisticated features, going in-depth to give you the knowledge you need. You will: Gain a solid architectural understanding of Entity Framework Core 2 Learn how to create databases using your MVC data model Learn how to create MVC models using an existing database Learn how to use Entity Framework Core 2 to access data in an MVC application Learn how to use Entity Framework in RESTful Web Services Each topic is covered clearly and concisely and is packed with the details you need to learn to be truly effective. The most important features are given a no-nonsense in-depth treatment and chapters include common problems and details of how to avoid them.